Pengembangan Wisata Religi Gua Maria Golo Curu di Kota Ruteng, Manggarai, Nusa Tenggara Timur - Yohana Stefania Hasiman; I Putu Anom (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2020)
Interesting tourist attractions that are not yet known by many people, one of them such as Maria Golo Curu Cave has a great opportunity to be used as a religious tourism destination in the City of Ruteng, Manggarai Regency, but a very unfortunate phenomenon that its development has not been maximized. The purpose of this study is to identify existing attractions, such as natural, cultural, artificial attractions and maximize the development of Golo Curu as a religious tourism destination by using SWOT analysis which is an analysis based on strengths, weaknesses, opportunities and threats. The results of the study concluded that, the advantage of the Golo Curu Maria Cave is the natural beauty that is still beautiful and unspoiled by human hands, not only as a place to pray but also as a place to relax and become a beautiful photo spot. The disadvantage is, access to the damaged and disturbing Golo Curu visitors, lack of maximum management and maintenance that is lacking, does not have parking space, and is associated with less commendable community ethics. Thus, the priority of developing religious tourism with the SWOT approach is to preserve the attractiveness and culture of religious activities, improve access to the Golo Curu, improve existing management, provide parking, support each organization participating in tourism activities, support existing tourism services so that the creation of tourism employment opportunities, involving rural communities in every decision-making and every tourism activity. Keywords: Attraction, Development, Religious Tourism, SWOT Approach